Neuropharmacognosy as an Emerging Multidisciplinary Science - Abdelaziz Ghanemi; Besma Boubertakh (Institute of Advanced Engineering and Science, 2014)
Neuropharmacognosy represents the field that combines neuroscience and pharmacognosy. It allows us to better understand and use the data that pharmacognosy provides and apply them in neurosciences which may lead to new therapeutic approaches.The existence of both pharmacological and toxicological aspects of neuropharmacognosy creates more challenges. However, the methodsprovided by the related fields, such as chemistry and biology, let us expect more advances and hopefully new perspective that would overcome the current challenges